Effects of graphene oxide on resistance to chloride ion penetration of concrete. Issue 19 (18th October 2022) - Luo, Surong; Li, Xin; Lin, Weiyi; Wang, Dehui
Abstract : The effects of graphene oxide (GO) on the microstructure and resistance to chloride ion (Cl− ) penetration of matrix containing 0-0.05% GO were investigated through isothermal calorimetry, thermogravimetric analysis, X-ray diffraction, mercury intrusion porosimetry and the rapid chloride penetration test method. A proper dosage of GO promoted the hydration process of cement, increased the calcium hydroxide (Ca(OH)2 ) content, refined the size of calcium hydroxide, promoted the formation of high-density calcium silicate hydrate and improved the pore size distribution of cement matrix. Compared to the group without GO, the porosity of concrete containing 0.03% GO decreased by 8.56%, the largest pore diameter decreased by 29.05% and pores larger than 50 nm were reduced by 36.93%. In addition, the incorporation of GO improved the resistance to chloride ion penetration of concrete. The charge passed through the concrete first decreased and then increased with the increasing GO dosage. When the dosage of GO was 0.03%, the charge passed through the concrete was 27.71% lower than that of the control group. There was a significant correlation between the permeability of chloride ions and pore structure, especially the proportion of pores larger than 50 nm of concrete.